Bio‐functional hydrogel with antibacterial and anti‐inflammatory dual properties to combat with burn wound infection - Yahui Xiong; Yingbin Xu; Fei Zhou; Yanke Hu; Jingling Zhao; Zhonghua Liu; Qiyi Zhai; Shaohai Qi; Zhaoqiang Zhang; Lei Chen (Wiley, 2023)
Abstract Burn infection delays wound healing and increases the burn patient mortality. Consequently, a new dressing with antibacterial and anti‐inflammatory dual properties is urgently required for wound healing. In this study, we propose a combination of methacrylate gelatin (GelMA) hydrogel system with silver nanoparticles embed in γ‐cyclodextrin metal-organic frameworks (Ag@MOF) and hyaluronic acid‐epigallocatechin gallate (HA‐E) for the burn wound infection treatment. Ag@MOF is used as an antibacterial agent and epigallocatechin gallate (EGCG) has exhibited biological properties of anti‐inflammation and antibacterial. The GelMA/HA‐E/Ag@MOF hydrogel enjoys suitable physical properties and sustained release of Ag+. Meanwhile, the hydrogel has excellent biocompatibility and could promote macrophage polarization from M1 to M2. In vivo wound healing evaluations further demonstrate that the GelMA/HA‐E/Ag@MOF hydrogel reduces the number of the bacterium efficiently, accelerates wound healing, promotes early angiogenesis, and regulates immune reaction. A further evaluation indicates that the noncanonical Wnt signal pathway is significantly activated in the GelMA/HA‐E/Ag@MOF hydrogel treated group. In conclusion, the GelMA/HA‐E/Ag@MOF hydrogel could serve as a promising multifunctional dressing for the burn wound healing.